Two new species records of Lecithoceridae (Gelechioidea: Lepidoptera) from India - Pathania, Prakash C.; Shashank, Pathour R.; Park, Kyu-Tek (Zootaxa, 2021)
The Dalma Wildlife Sanctuary, located in the Dalma Hills about 10 km north of the city of Jamshedpur, Jharkhand, India, is topographically and climatically unique. It encompasses a forested area of over 195 km2 east of the Singhbhum and Saraikela-kharsawan districts of Jharkhand, extending from Chandil about 40 km eastward, running nearly parallel to the National Highway-33 at an altitude of about 280 m. The forests of the sanctuary are "dry peninsular sal" and "northern dry mixed deciduous forest".